#### Answer

$r = \frac{A-P}{Pt}$

#### Work Step by Step

A = P + Prt
A- P = (Pt)r
$r = \frac{A-P}{Pt}$

Chegg costs money, GradeSaver solutions are free!

Published by
Cengage Learning

ISBN 10:
9781337271172

ISBN 13:
978-1-33727-117-2

$r = \frac{A-P}{Pt}$

A = P + Prt
A- P = (Pt)r
$r = \frac{A-P}{Pt}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.